P. K. Page’s and Ricardo Sternberg’s Brazil poems: visitor’s gaze and sentimento íntimo - Martins, Maria Lúcia Milléo (Letras de Hoje, 2015)
Abstract: Poets P. K. Page and Ricardo Sternberg depict significant traits of Brazilian culture in their writings. Page lived in Brazil in the fifties accompanying her husband in his posting as ambassador; Sternberg was born in Rio and left the country in the sixties, constantly returning to his roots since then. In their portraits of Brazil, private memories mingle with the country’ s cultural history. Considering implications of gaze and what Stuart Hall calls “positions of enunciation” in cultural representations, this study discusses Page’ s visitor’ s gaze and Sternberg’ s sentimento íntimo in their depictions of Brazil. The selection of poems extends from early publications to more recent ones – Sternberg’ s Bamboo Church (2003), and Page’ s Hand Luggage, A Memoir in Verse (2006). Keywords: P. K. Page; Ricardo Sternberg; Cultural representation; Poetry; Brazil. ************************************************************************************************************************************************************************************************************ Poemas do Brasil de P. K. Page e Ricardo Sternberg: olhar de visitante e sentimento íntimo Resumo: Os poetas P. K. Page e Ricardo Sternberg registram traços significativos da cultura brasileira em seus escritos. Page morou no Brasil nos anos 50 acompanhando o marido em seu posto de embaixador; Sternberg nasceu no Rio e deixou o país nos anos 60, constantemente retornando às origens desde então. Em seus retratos de Brasil, memórias particulares se misturam à história cultural do país. Considerando implicações do olhar e o que Stuart Hall chama de “posições de enunciação” em representações culturais, esse estudo discute o olhar de visitante de Page e o “sentimento íntimo” de Sternberg em seus retratos de Brasil. A seleção de poemas se estende das primeiras publicações às mais recentes – Bamboo Church (2003) de Sternberg e A Memoir in Verse (2006) de Page. Palavras-chave: P. K. Page; Ricardo Sternberg; Representação cultural; Poesia; Brasil.